One year of breast cancer in Ibadan, Southwestern Nigeria: a histopathological review (2021)
Background: Breast cancer is a major public health problem in most low- to medium-income countries of the world because of its high morbidity and mortality rate. Histopathological features are vital in risk assessment, selection of treatment and prognostication in breast cancer patients. This study aimed to assess the histopathological features of all breast cancer cases seen in a tertiary hospital in the year 2018. Methods: This is a retrospective review of all breast cancer cases histologically diagnosed and confirmed by three Pathologists at the University College Hospital (UCH), Ibadan over a one-year period from 1st January 2018 to 31st December, 2018. Results: A total of 236 breast cancer cases were seen during this period, 234 (99.2%) were females while only 2 (0.8%) were male. 163 (69.7%) patients were between the fourth and sixth decades of life, 65 (27.8%) patients were above sixth decade while 6 (2.5%) patients were below fourth decade. Invasive ductal carcinoma of No Special Type (NST) was the commonest histological subtype 212 (89.8%). Grade 1 cases were 25 (10.6%), Grade 2 129 (54.7%) and Grade 3 cases were 40 (16.9%) while 42 (17.8%) were not graded. Lymphovascular invasion observed in 98 (41.5%) of the cases. 54 (22.9%) had immunohistochemistry out of which 23 (43.4%) were triple negative while 8 (3.4%) were triple positive. Conclusion: Histopathological features suggesting aggressive disease was predominantly observed. Efforts should be made towards early diagnosis, adequate evaluation and prompt treatment. Cancer care should be fully incorporated in the National Health Insurance Scheme (NHIS).